Replacing home : from primordial hut to digital network in contemporary art - Johung, Jennifer (University of Minnesota Press, 2012)
From property deeds to shipping containers to wearable shelters to virtual spaces: what does it mean to draw a spatial boundary? To be at home? In a world in which notions of place are constantly changing, this book looks at new constructions of staying in place - in contemporary site-specific art, digital media, portable architecture, and various other imaginable shelters and sites. The book suggests that while 'place' may no longer be a sustainable category, being in place and belonging at home are nonetheless possible.